TIME PETRI NET METHOD APPLICATION TO MINIMIZE INVESTMENT COST OF BATCH PROCESS BASED PLANT DEVELOPMENT - Jaka Lelana; Bobby O.P. Soepangkat (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2012)
Companies’ effort to reduce all cost including the production cost has become important due to increasing competition in the chemical industry today. One of the efforts is to decrease the investment cost of plant development in order to increase the return of investment. The amount of equipment minimization will also reduce the investment cost. Timed Petri nets method has been adopted in this study to minimize investment cost for batch process in PT ENG. The first step was to examine the utilization rate of equipment on an existing process. The second, was to add some equipment in the existing process, it was also examine the utilization and production capacity result. The first and second step has analysed by using time Petri nets. The final step was to conduct feasibility study by calculating the cost investment, payback period and return on investment. Plant development by TPN method has doubled production capacity, whereas the requirement of investment cost for development was US 831,881 or 21.1% of the investment cost prior to development. It was found that payback period (PBP) was 1.99 years or 54.37% faster and return on investment (ROI) was 50.4% or 2.02 times higher than the existing multiplication development method.